Gallic Acid Alleviates Neuropathic Pain Behaviors in Rats by Inhibiting P2X7 Receptor-Mediated NF-κB/STAT3 Signaling Pathway - Yang, Runan; Li, Zijing; Zou, Yuting; Yang, Jingjian; Li, Lin; Xu, Xiumei; Schmalzing, Günther; Nie, Hong; Li, Guilin; Liu, Shuangmei; Liang, Shangdong; Xu, Changshui (Frontiers in Pharmacology, 2021)
Neuropathic pain is a complex disease with high incidence. Adenosine triphosphate (ATP) and its activated P2X7 receptor are involved in the signal transmission of neuropathic pain. Gallic acid (3,4,5-trihydroxybenzoic acid) is a traditional Chinese medicine obtained from natural plants that exhibit anti-inflammatory, analgesic, and antitumor effects. However, the underlying mechanism for gallic acid in analgesia remains unknown. This study aims to reveal how gallic acid alleviates neuropathic pain behaviors in a rat model with chronic constriction injury (CCI). Real-time PCR, western blotting, double-label immunofluorescence, molecular docking, and whole-cell patch clamp technology were used to explore the therapeutic action of gallic acid on neuropathic pain. The results showed that after CCI rats were treated with gallic acid for 1 week, the mechanical withdrawal threshold and thermal withdrawal latency were increased, accompanied by inhibition of the upregulated expression of P2X7 and TNF-α at both mRNA and protein levels, and reduced NF-κB and phosphorylated-STAT3 in the dorsal root ganglia. At the same time, gallic acid significantly decreased the coexpression of P2X7 and glial fibrillary acidic protein in the dorsal root ganglia. In addition, gallic acid could suppress ATP-activated current in human embryonic kidney 293 (HEK293) cells transfected with the plasmid expressing P2X7 but had no effect on ATP activation current of P2X7-mutant plasmid (with the point mutation sequence of the key site where gallic acid binds to the P2X7 receptor). Therefore, our work suggests that gallic acid may alleviate neuropathic pain in CCI rats by inhibiting the P2X7 receptor and subsequent activation of the TNF-α/STAT3 signaling pathway.